Predictors of the development of retinal vascular diseases in women after preeclampsia - O.V. Kolenko; E.L. Sorokin; N.S. Khodzhaev; N.V. Pomytkina; G.V. Chizhova; A.A. Fil'; Ya.E. Pashentsev (РМЖ "Клиническая офтальмология")
O.V. Kolenko1,2, E.L. Sorokin1,3, N.S. Khodzhaev4, N.V. Pomytkina1, G.V. Chizhova2, A.A. Fil1, Ya.E. Pashentsev1 1Khabarovsk branch of S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Khabarovsk, Russian Federation 2Postgraduate Institute for Public Health Professionals, Khabarovsk, Russian Federation 3Far Eastern State Medical University, Khabarovsk, Russian Federation 4S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation Background: in recent years, retinal vascular diseases occur more frequently, in particular, in younger individuals. Aim: to assess choroidal blood flow in pregnant women with preeclampsia and after birth. Materials and Methods: 42 pregnant women with preeclampsia aged 21–40 years were included in the study group. 30 women with normal pregnancy aged 19–38 years were included in comparison group 1. 27 women without pregnancy aged 35–57 years with vascular diseases of posterior eye segment were included in comparison group 2. Controls were 25 healthy age-matched (19–43 years) women without pregnancy. Linear blood flow velocity in short posterior ciliary arteries and prothrombin index were measured in all women. Results: reduced linear blood flow velocity in short posterior ciliary arteries in the third trimester of pregnancy was revealed in pregnant women with preeclampsia. However, in 6 to 8 months after birth these parameters have returned to normal values. In 12 women, these parameters were still low while prothrombin index was high. Retinal vein occlusions occurred in all these women after 6.5 to 8.5 years. Conclusion: our findings demonstrate that measurin g linear blood flow velocity in short posterior ciliary arteries and prothrombin index in pregnancy complicated with preeclampsia as well as within a year after birth may help to identify risk groups for vascular retinal diseases. Keywords: choroidal blood flow, short posterior ciliary arteries, pregnancy, preeclampsia, prothrombin index, vascular retinal diseases, retinal vein occlusion. For citation: Kolenko O.V., Sorokin E.L., Khodzhaev N.S. et al. Predictors of the development of retinal vascular diseases in women after preeclampsia. Russian Journal of Clinical Ophthalmology. 2019;19(4):189–194.